Comparison of a traditional and non‐traditional residential care facility for persons living with dementia and the impact of the environment on occupational engagement. (10th November 2015) - Richards, Kieva; D'Cruz, Rachel; Harman, Suzanne; Stagnitti, Karen
Abstract : Background: Dementia residential facilities can be described as traditional or non‐traditional facilities. Non‐traditional facilities aim to utilise principles of environmental design to create a milieu that supports persons experiencing cognitive decline. This study aimed to compare these two environments in rural Australia, and their influence on residents' occupational engagement. Methods: The Residential Environment Impact Survey (REIS) was used and consists of: a walk‐through of the facility; activity observation; interviews with residents and employees. Thirteen residents were observed and four employees interviewed. Resident interviews did not occur given the population diagnosis of moderate to severe dementia. Descriptive data from the walk‐through and activity observation were analysed for potential opportunities of occupational engagement. Interviews were thematically analysed to discern perception of occupational engagement of residents within their facility. Results: Both facilities provided opportunities for occupational engagement. However, the non‐traditional facility provided additional opportunities through employee interactions and features of the physical environment. Interviews revealed six themes: Comfortable environment; roles and responsibilities; getting to know the resident; more stimulation can elicit increased engagement; the home‐like experience and environmental layout. These themes coupled with the features of the environment provided insight into the complexity of occupational engagement within this population. Conclusion: This study emphasises the influence of the physical and social environment on occupational engagement opportunities. A non‐traditional dementia facility maximises these opportunities and can support development of best‐practice guidelines within this population.